THE EFFECT OF APPLYING INSIDE OUTSIDE CIRCLE METHOD ON STUDENTS’ SPEAKING ABILITY AT SMP ISLAM AS-SHOFA PEKANBARU - Ramadhani, Intan Rezki; Jismulatif, Jismulatif; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to discover the effect of Inside Outside Circle Method on the speaking ability of the first year students of SMP Islam As Shofa Pekanbaru academic year 2018/2019. The sample of this research was VII 4 students which consisted of 27 students. The sample was selected by using cluster random sampling technique. This research is pre-experimental and the data were collected by means of pre-test and post-test design in the form of speaking test which focused on describing objects. The data were analyzed using five components of speaking: pronunciation, grammar, vocabulary, fluency, and comprehension. The results showed that the score of the pretest was 39,60 and the post-test was 65,58 while the difference from both scores was 25,98. Therefore, it can be concluded that there is a significant effect of Inside Outside Circle Method on the speaking ability of the first year students of SMP Islam As Shofa Pekanbaru. In other words, the teaching of speaking through Inside Outside Circle Method, as one of the alternative speaking activities, has an effect on the students’ speaking ability.Keywords: Inside Outside Circle Method, Speaking Ability